Evaluating Quality in Agile Developments. A first validation experience with NEA Software SMEs - Pinto, Noelia (2017)
To obtain products of high quality software it is necessary to carry out good processes management in which measurement is a key factor. Therefore, companies should focus on continuous improvement cycles that integrate both the development process and the product obtained, to increase quality in both aspects. This cycle of improvement involves the adoption of a quality model appropriate to the characteristics of the company and a methodology that guides the software development cycle. In this sense, the agile philosophy proves to be the most suitable approach for the current development environments, and they are positioned as an alternative to the development processes with high cost in documentation and excessively long processes. This paper presents the results obtained by automation of QuAM Model for the quality evaluation of agile projects on actual production environments and the subsequent analysis based on these projects.